ANALYSIS OF FACTORS IN THE INTEREST OF KSPPS BINAMA MEMBERS IN CHOOSING MURABAHAH AGREEMENT FINANCING - Veda Prasetyo, Kiki Andhika; Iswanaji, Chaidir; Pramudyastuti, Octavia Lhaksmi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The aim of this research is to identify the factors that influence members in choosing murabahah financing. This type of research uses qualitative research with a case study approach. Collecting the data produced in this research, the author conducted interviews with members and employees of the financing services office regarding the factors that influence a member to choose financing with a murabahah agreement. Based on the results of research that has been carried out, there are several factors that influence a member to choose murabahah financing, namely the financing factor in accordance with Islamic sharia, the factor that is cheaper than leasing, the trust factor. Based on the financing arrangements conducted for the implementation of the murabahah contract at KSPPS BINAMA Magelang Branch, it can be inferred that the institution plays a multifaceted role as a sharia-based cooperative, distributing financing to communities utilizing murabahah agreements while also serving as a financing provider and member companion. This is evidenced by member testimonials affirming the efficacy of KSPPS BINAMA's lending activities in supporting MSME development and meeting their needs, coupled with the commendable and amicable service provided by the cooperative.